Community-acquired pneumonia in patients with bacterial meningitis: a prospective nationwide cohort study. (April 2020) - Figueiredo, A.H.A.; Brouwer, M.C.; Bijlsma, M.W.; van der Ende, A.; van de Beek, D.
Abstract: Objective: Pneumonia is considered a focus of infection in patients presenting with community-acquired bacterial meningitis but the impact on disease course is unclear. The aim was to study presenting characteristics, clinical course and outcome of meningitis patients with co-existing pneumonia on admission. Methods: We evaluated adult patients with community-acquired bacterial meningitis with pneumonia on admission in a nationwide, prospective cohort performed from March 2006 to June 2017. We performed logistic regression analysis to identify clinical characteristics predictive of pneumonia on admission, and to quantify the effect of pneumonia on outcome. Results: Pneumonia was diagnosed on admission in 315 of 1852 (17%) bacterial meningitis episodes and confirmed by chest X-ray in 256 of 308 (83%) episodes. Streptococcus pneumoniae was the causative organism in 256 of 315 episodes (81%). Pneumonia on admission was associated with advanced age (OR 1.03 per year increase, 95% CI 1.02–1.04, p < 0.001), alcoholism (OR 1.96, 95% CI 1.23–3.14, p 0.004), cancer (OR 1.54, 95% CI 1.12–2.13, p 0.008), absence of otitis or sinusitis (OR 0.44, 95% CI 0.32–0.59, p < 0.001) and S. pneumoniae (OR 2.14, 95% CI 1.55–2.95, p < 0.001) in the multivariate analysis. An unfavourable outcome defined as a score of 1–4 on the Glasgow Outcome Scale was observed in 172 (55%) episodes and 87 patients (28%) died. Pneumonia on admission was independently associated with unfavourable outcome and mortality in the multivariate analysis (OR 1.48, 95% CI 1.12–1.96; p 0.005). Conclusion: Pneumonia on admission in bacterial meningitis is a frequent coexisting infection and is independently associated with unfavourable outcome and mortality.